Expert System for Energy Management of Electric Cars - Papadimitropoulos, J. T.; Chondros, Thomas G.; Panteliou, Sofia; Carlsson, Bengt; Kalogirou, Soteris A.; Dimarogonas, Andrew D. (My University, 1999)
An expert system capable of learning from the electric car operation is used to evaluate the drive train performance and energy management and furthermore, monitor faults. This system using the computational power of modern portable personal computers, user-friendly data input and output, and full-screen editor capabilities is used for on-board drive train monitoring, energy management optimization, and fault diagnosis.
Keywords: Artificial Neural Network; Electric car; Energy